Kinetics of m-xylene in man – influence of intermittent physical exercise and changing environmental concentrations on kinetics - Riihimäki, Vesa; Pfäffli, Pirkko; Savolainen, Kai (Scandinavian Journal of Work, Environment & Health, 1979)
Volunteer subjects were exposed to m-xylene 6 hid over five successive days under the following types of environmental conditions: exposure type I: constant xylene concentration in air, subjects performed periodic ergometer exercise at 100 W; exposure type II: varying xylene concentration in air with peak levels coinciding with periodic ergometer exercise; and exposure type III: constant xylene concentration in air, subjects sedentary. The three types of exposure were identical in that the time-weighted averages of the xylene concentrations in the air inhaled over the whole day were about the same (in most cases 4.1 mmol/m3). Nevertheless, the daily xylene uptakes proved to be somewhat different, while the maximum rates of xylene uptake occurring in the three exposure types were markedly different. In exposure types I and II the main part of the day`s xylene uptake took place during the repeated short exercise sessions and resulted, partly due to an altered distribution of organ blood flow, in a greater distribution of xylene to tissues with slow elimination characteristics (and a greater cumulation of xylene) than in exposure type III. Although relatively high pulmonary uptake rates of xylene (about 150-300 µmol/min) were estimated to have occurred over 15-min periods at a time, no signs of saturation kinetics were noted. The relative contributions of the two biotransformation pathways of m-xylene (side-chain oxidation and aromatic oxidation) were not markedly altered by the different environmental conditions, but aromatic oxidation, producing 2,4 xylenol, tended to increase slightly over the five exposure days. The blood xylene levels attained under stable near-equilibrium conditions and under conditions of greatly increased uptake appeared to be directly related to the rate of xylene uptake, whereas no such relation existed in the phase of decreasing xylene uptake.
Keywords: environmental concentration; human exposure; intermittent physical exercise; kinetics; m-xylene; man; men; physical exercise